Value-Competence Based Synergy in the Design and Implementation of University Educational Programs - V. M. Florea; O. A. Volkova; L. A. Kravtsova (Высшее образование в России)
The article discusses the use of value-competence based approach in designing and implementing university educational programs on an example of educational process in Ukhta State Technical University. The value-competence based approach is designed to provide training of highly professional specialists who are in demand by employers and are competitive in the labor market. The University aims at creating a convergent path for the implementation of learning and educational processes. A mandatory condition of value-competence based synergy in University educational environment is a focus on the conjunction of professional competencies and student’s personal values. As a result, students become active participants in the educational process